Organic Slurry with Gradient Volatilization Rate and Preparation Method

The gradient volatilization rate organic slurry addresses the issue of uneven volatilization in screen printing by using specific compositions and processes, ensuring efficient and uniform film formation for neodymium iron-boron magnets.

KR103043051B1Active Publication Date: 2026-11-03GRIREM ADVANCED MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240047133
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-04-28
Filing Date
2024-04-08
Publication Date
2026-11-03
Estimated Expiration
2044-04-08

AI Technical Summary

Technical Problem

Existing screen printing methods for neodymium iron-boron magnets face challenges with organic slurries that either have fast room-temperature volatilization rates causing screen clogging or slow high-temperature volatilization rates leading to non-uniform films, which affect diffusion efficiency and quality.

Method used

A gradient volatilization rate organic slurry comprising rare earth powders, organic solvents, resins, dispersants, and anti-settling agents, with specific weight percentages and manufacturing processes to achieve uniformity and controlled volatilization rates.

Benefits of technology

The slurry ensures low volatilization at room temperature to prevent screen clogging and high volatilization at high temperature for efficient drying, improving processing efficiency and reducing impurity introduction during curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112024038564332-PAT00001_ABST
    Figure 112024038564332-PAT00001_ABST
Patent Text Reader

Abstract

Embodiments of the present invention disclose an organic slurry having a gradient volatilization rate and a method for manufacturing it. The organic slurry comprises rare earth powder, an organic solvent, and a resin, and further comprises a dispersant and / or an antisediment and / or a synergist, wherein the weight percentages of each component are: the rare earth powder is 50% to 90%; the organic solvent is 8% to 50%; the resin is 0.4% to 6%; the dispersant is 0% to 5%; the antisedimentist is 0% to 3%; and the synergist is 0% to 3%. The manufacturing method comprises weighing the rare earth powder, organic solvent, resin, dispersant and / or antisediment and / or synergist according to their respective weight percentages; placing each weighed component into a stirrer and stirring under constant temperature conditions, and then cooling to room temperature to obtain an organic carrier; placing the organic carrier and the weighed rare earth powder into a vacuum high-speed disperser to obtain a coarse organic slurry; The above-mentioned coarse organic slurry is transferred to a three-roll grinder with adjustable spacing and ground to obtain a fine organic slurry. The present invention can realize gradient volatilization of the slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to the field of screen printing technology, and in particular to an organic slurry having a gradient volatilization rate and a method for manufacturing it. Background Technology

[0002] Since its discovery in the 1980s, Neodymium Iron-Boron (NdFeB) permanent magnet materials have been widely used in the electronic information, medical, and other fields due to their excellent properties, such as high remanence, coercivity, and maximum magnetic energy product. In recent years, to meet the performance requirements of drive motors for new energy vehicles and direct-drive permanent magnet devices for wind power generation using sintered Neodymium Iron-Boron magnets, it is generally necessary to perform grain boundary diffusion treatment on the magnets to improve their coercivity. Traditional grain boundary diffusion mostly utilizes heavy rare earth elements, fluorides, hydrides, oxides, and alloys as diffusion sources, and the diffusion sources are coated onto the magnet surface using methods such as sputtering, deposition, electrophoresis, surface coating, and immersion. However, the aforementioned diffusion sources have low diffusion efficiency, and the lack of low-cost grain boundary diffusion processes suitable for high-capacity, industrialized mass production, and stable production limits the development, application, and dissemination of high-grade Neodymium Iron-Boron magnets.

[0003] To overcome the shortcomings of existing grain boundary diffusion methods, screen printing technology is being applied to the neodymium iron-boron industry. Screen printing refers to a printing process using a scraper that utilizes a screen stencil and a slurry, allowing the slurry to pass through the holes of the stencil and be printed onto the printed material. Screen printing integrates the advantages of sputtering and surface coating methods and possesses characteristics such as low cost, high production efficiency, and the ability to easily achieve automated production; it is expected to develop into the mainstream process for neodymium iron-boron grain boundary diffusion. The slurry serves as a raw material for screen printing and directly influences the printing and subsequent diffusion effects.

[0004] Among existing technologies, the method for manufacturing slurries mainly involves dispersing rare earth powders in organic solutions such as alcohol or acetone through stirring. Organic slurries are difficult to simultaneously satisfy both slow room-temperature volatilization rates and fast high-temperature volatilization rates. Because the volatilization rate at room temperature is fast, a large amount of the organic solvent in the slurry volatilizes during the printing process, and the viscosity of the organic slurry increases, making it difficult to remove from the screen; if the volatilization rate at high temperature is slow, not only does the drying time increase, but flow of the coating film occurs, which ultimately results in a non-uniform film and affects the diffusion effect. The problem to be solved

[0005] The objective of the present invention is to provide an organic slurry having a gradient volatilization rate and a method for manufacturing it, which can be used to solve at least one technical problem and realize gradient volatilization of the slurry.

[0006] An embodiment of the present invention is realized as follows:

[0007] An organic slurry having a gradient volatilization rate comprises a rare earth powder, an organic solvent, and a resin, and further comprises a dispersant and / or an antisedimentation agent and / or a booster, wherein the weight percentage of each component is:

[0008] The rare earth powder is 50% to 90%;

[0009] The organic solvent is 8% to 44%;

[0010] Suzy is 0.4%~6% and;

[0011] The dispersant is 0% to 5%;

[0012] The anti-settling agent is 0% to 3%;

[0013] The increase rate is 0% to 3%.

[0014] In a preferred embodiment of the present invention, the organic slurry for neodymium iron boron screen printing comprises, wherein the rare earth powder comprises one or two mixtures of pure metal powder of a heavy rare earth element, alloy powder containing a heavy rare earth or light rare earth element, and heavy rare earth powder containing a hydride, fluoride, and oxide of a heavy rare earth element.

[0015] In a preferred embodiment of the present invention, the pure metal powder in the neodymium iron boron screen printing organic slurry comprises one or two of Tb, Dy, Ho, and Gd, or a mixture of various types.

[0016] The above alloy powder is composed of RexMy in mass percentage, where RE is one or two or a mixture of various of Tb, Dy, Ho, Gd, Pr, Nd, La, Ce, and Y, and M is one or two or a mixture of various of Ga, Cu, Al, Ni, and Fe, and 60≤x≤95, 5≤y≤40.

[0017] In a preferred embodiment of the present invention, the particle size of the rare earth powder in the neodymium iron boron screen printing organic slurry is D50 < 3 μm.

[0018] In a preferred embodiment of the present invention, the organic solvent in the neodymium iron boron screen printing organic slurry comprises one or two or various mixtures of propylene glycol phenyl ether, DBE (dibasic acid ester), methyl isobutanone, and propylene glycol methyl ether acetate.

[0019] In a preferred embodiment of the present invention, the resin in the organic slurry for neodymium iron boron screen printing comprises one or two or various mixtures of ethylcellulose, polyvinyl butyral, acrylic resin, vinyl chloride resin, polyester resin, and polyurethane.

[0020] The technical effect of this is: the resin improves the adhesion to the substrate of the organic slurry, thereby ensuring a subsequent grain boundary diffusion effect.

[0021] In a preferred embodiment of the present invention, the dispersant in the neodymium iron boron screen printing organic slurry comprises one or two or various mixtures of polyvinyl butyral, polyvinyl pyrrolidone, sodium polyacrylate, and polyvinylamide.

[0022] The technical effect of this is: the dispersant prevents the diffusion source powder in the organic slurry from re-aggregating, lowers the fineness of the organic slurry itself, and improves the consistency of weight gain during screen printing.

[0023] In a preferred embodiment of the present invention, the anti-settling agent in the neodymium iron boron screen printing organic slurry comprises one or two of polyamide wax, polyethylene wax, organic bentonite, fumed silica, or a mixture of various materials.

[0024] The technical effect of this is: the above anti-settling agent improves the static stability of the organic slurry, suppresses the layering phenomenon, and further lowers the volatilization rate at room temperature.

[0025] In a preferred embodiment of the present invention, the synergist in the neodymium iron boron screen printing organic slurry is one of a modified polyhydroxycarboxylic acid ester, BYK-SYNERGIST 2105, and BYK-SYNERGIST 2100.

[0026] Or it is a mixture of two or several.

[0027] The technical effect of this is: the above-mentioned synergist can improve the network structure of the organic carrier.

[0028] In a preferred embodiment of the present invention, the weight percentage of each component in the neodymium iron boron screen printing organic slurry is:

[0029] The pure metal powder is 65% to 75%;

[0030] One or two or more of propylene glycol phenyl ether, DBE, and propylene glycol methyl ether acetate are 10% to 30%;

[0031] One or two or more of ethylcellulose, polyvinyl butyral, and polyester resin are 0.4 to 4%;

[0032] One or two or more of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide are 0% to 3%;

[0033] One or two or more of the modified polyhydroxycarboxylic acid esters, BYK-SYNERGIST 2105, and BYK-SYNERGIST 2100 are 0% to 2%.

[0034] In a preferred embodiment of the present invention, the weight percentage of each component in the neodymium iron boron screen printing organic slurry is:

[0035] The alloy powder is 70% to 80%;

[0036] One or both or a combination of propylene glycol phenyl ether, DBE, and propylene glycol methyl ether acetate is 20%-30%;

[0037] One or two or more of acrylic resin, polyurethane, and polyester resin are 0.4% to 5%;

[0038] One or two or more of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide are 0% to 3%;

[0039] One or both of polyamide wax and polyethylene wax are 0% to 2%.

[0040] One or two or more of the modified polyhydroxycarboxylic acid esters, BYK-SYNERGIST 2105, and BYK-SYNERGIST 2100 are 0% to 2%.

[0041] In a preferred embodiment of the present invention, the weight percentage of each component in the neodymium iron boron screen printing organic slurry is:

[0042] The heavy rare earth powder is 60% to 80%;

[0043] One or both of DBE and propylene glycol methyl ether acetate are 10%-30%;

[0044] One or two or more of vinyl chloride resin, polyester resin, and polyurethane are 0.4~4%;

[0045] One or two or more of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide are 0% to 3%;

[0046] One or both of polyamide wax and polyethylene wax are 0% to 2%;

[0047] One or two or more of the modified polyhydroxycarboxylic acid esters, BYK-SYNERGIST 2105, and BYK-SYNERGIST 2100 are 0% to 2%.

[0048] A method for manufacturing an organic slurry having the above-mentioned gradient volatilization rate comprises the following:

[0049] Rare earth powder, organic solvent, resin, dispersant and / or antisettling agent and / or booster are each weighed according to weight percentage.

[0050] The weighed rare earth powder, organic solvent, resin, dispersant and / or antisediment and / or booster are sequentially placed into a stirrer and stirred at a speed of 600 r / min to 1200 r / min for 0.25 to 6 hours under constant temperature conditions of 20 to 70℃, and then cooled to room temperature to obtain an organic carrier.

[0051] The technical effect of this is: the manufactured organic carrier is uniform and free of aggregated substances.

[0052] The above organic carrier and weighed rare earth powder are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 1000 r / min to 4000 r / min for 0.25 to 1 hour to obtain a coarse organic slurry.

[0053] The technical effect of this is: the manufactured coarse organic slurry is bubble-free and uniformly dispersed.

[0054] The above coarse organic slurry is transferred to a three-roll grinder with adjustable spacing and ground 1 to 3 times to obtain a fine organic slurry.

[0055] The technical effect of this is: the fineness of the manufactured fine organic slurry is less than 5 μm.

[0056] The beneficial effects of the embodiments of the present invention are:

[0057] The organic slurry having a gradient volatilization rate and the manufacturing method of the present invention form a gradient of organic components and, with the help of strong interaction of abrasion, cause the organic carrier to form a network structure, ensuring that the volatilization rate at room temperature is less than 0.05% / h and the volatilization rate at high temperature of 120°C is 1.2% / h or more, thereby realizing gradient volatilization of the slurry. The manufactured organic slurry for screen printing of rare earth permanent magnet materials has a low volatilization rate at room temperature, so it can effectively prevent problems such as screen clogging and printing non-uniformity caused by the volatilization of the organic solvent during printing; at high temperature, the organic slurry has a high volatilization rate and a short curing time, which significantly shortens the drying time, improves processing efficiency, and reduces the content of impurities such as oxygen and carbon introduced into the magnet during the curing and subsequent heat treatment steps. Brief explanation of the drawing

[0058] In order to more clearly explain the technical solution of the embodiments of the present invention, the drawings necessary for the embodiments are briefly introduced below. The drawings below represent only some embodiments of the present invention and should not be considered as limiting the scope, and a person skilled in the art can obtain other related drawings based on these drawings without performing creative labor. FIG. 1 is a flowchart of a method for manufacturing an organic slurry having a gradient volatilization rate according to the present invention; FIG. 2 is a guide diagram of the volatilization curve of an example of an organic slurry having a gradient volatilization rate according to the present invention, which is held at 40, 80, and 120°C for 2 hours; FIG. 3 is a guide diagram of the volatilization curve of a comparative example of an organic slurry having a gradient volatilization rate according to the present invention, which was heated at 40, 80, and 120°C for 2 hours; FIG. 4 is a guide diagram of a photograph of a coating surface gold after drying an example of an organic slurry having a gradient volatilization rate of the present invention at 120°C for 10 minutes. Specific details for implementing the invention

[0059] In order to clarify the purpose, technical solution, and advantages of the embodiments of the present invention, the technical solution within the embodiments of the present invention is described more clearly and completely below by combining the drawings thereof. It should be noted that the described embodiments are partial embodiments of the present invention, not all embodiments. The components of the embodiments of the present invention described and presented herein may be arranged and designed in various configurations.

[0060] An organic slurry having a gradient volatilization rate provided in the first embodiment of the present invention comprises a rare earth powder, an organic solvent, and a resin, and further comprises a dispersant and / or an antisedimentation agent and / or a promoter, wherein the weight percentage of each component is:

[0061] The rare earth powder is 50% to 90%;

[0062] The organic solvent is 8% to 44%;

[0063] Suzy is 0.4%~6% and;

[0064] The dispersant is 0% to 5%;

[0065] The anti-settling agent is 0% to 3%;

[0066] The increase rate is 0% to 3%.

[0067] Preferably, the weight percentage of each component is:

[0068] The rare earth powder is 60% to 80%;

[0069] The organic solvent is 10% to 30%;

[0070] Suzy is 0.4%~5% and;

[0071] The dispersant is 0% to 3%;

[0072] The anti-settling agent is 0% to 2%;

[0073] The increase rate is 0% to 2%.

[0074] In a preferred embodiment of the present invention, the rare earth powder in the neodymium iron boron screen printing organic slurry comprises one or two mixtures of pure metal powder of a heavy rare earth element, alloy powder containing a heavy rare earth or light rare earth element, and heavy rare earth powder containing a hydride, fluoride, and oxide of a heavy rare earth element.

[0075] In a preferred embodiment of the present invention, the pure metal powder in the neodymium iron boron screen printing organic slurry comprises one or two of Tb, Dy, Ho, and Gd, or a mixture of various types.

[0076] The above alloy powder is composed of RexMy in mass percentage, where RE is one or two or a mixture of various of Tb, Dy, Ho, Gd, Pr, Nd, La, Ce, and Y, and M is one or two or a mixture of various of Ga, Cu, Al, Ni, and Fe, and 60≤x≤95, 5≤y≤40.

[0077] In a preferred embodiment of the present invention, the pure metal powder in the neodymium iron boron screen printing organic slurry comprises one or both of Tb and Dy.

[0078] The above alloy powder consists of RexMy in mass percentage, where RE is one, two, or a mixture of Tb, Dy, Pr, and Nd. When RE is Tb, M is one, two, or a mixture of Ga, Cu, Al, and Ni, with 70≤x≤90 and 10≤y≤30; when RE is Dy, M is one, two, or a mixture of Ni, Fe, and Ga, with 60≤x≤80 and 20≤y≤40; when RE is two or three of Tb, Pr, and Nd, M is one or two mixtures of Cu and Al, with 80≤x≤95 and 5≤y≤20. The addition of the above alloy elements lowers the melting point of the diffusion source and changes the diffusion from solid-liquid diffusion to liquid-liquid diffusion, thereby significantly improving diffusion efficiency. Furthermore, after diffusing into the interior of the magnet, the above alloy elements are widely distributed at the grain boundaries, which can reduce magnetic exchange bonding between particles.

[0079] In a preferred embodiment of the present invention, the particle size of the rare earth powder in the neodymium iron boron screen printing organic slurry is D50 < 3 μm.

[0080] Preferably, the particle size of the rare earth powder is 1.6 <D50<2.4이다. 분말 입경이 해당 범위 내에 위치할 때, 우수한 안정성을 얻을 수 있는 동시에, 분말의 입경이 너무 작아서, 분말 제조 효율이 심각하게 저하되는 것을 초래하지 않는다.

[0081] In a preferred embodiment of the present invention, the organic solvent in the neodymium iron boron screen printing organic slurry comprises one or two or various mixtures of propylene glycol phenyl ether, DBE, methyl isobutanone, and propylene glycol methyl ether acetate.

[0082] Preferably, the organic solvent is one or two or several mixtures of propylene glycol phenyl ether, DBE, and propylene glycol methyl ether acetate, and the organic solvent easily volatilizes at high temperatures, thereby improving drying efficiency after screen printing, reducing the inflow of impurities such as C and O into the magnet during grain boundary diffusion, and ensuring the performance of the magnet after diffusion.

[0083] In a preferred embodiment of the present invention, the resin in the organic slurry for neodymium iron boron screen printing comprises one or two or various mixtures of ethylcellulose, polyvinyl butyral, acrylic resin, vinyl chloride resin, polyester resin, and polyurethane.

[0084] Preferably, the resin is one or two or a mixture of polyvinyl butyral, vinyl chloride resin, polyester resin, and polyurethane, and the resin has a large molecular weight, and even a small amount of addition can significantly increase the viscosity of the organic slurry, has a low thermal decomposition fraction, and reduces the entry of C and O elements into the magnet during grain boundary diffusion treatment.

[0085] The technical effect of this is: the above resin improves the adhesion of the organic slurry to the substrate, thereby ensuring a subsequent grain boundary diffusion effect.

[0086] In a preferred embodiment of the present invention, the dispersant in the neodymium iron boron screen printing organic slurry comprises one or two or various mixtures of polyvinyl butyral, polyvinyl pyrrolidone, sodium polyacrylate, and polyvinylamide.

[0087] Preferably, the dispersant is one or two or several mixtures of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide, and the dispersant is easily soluble in organic solvents and has excellent wettability for the diffusion source powder, which is advantageous for the dispersion of the diffusion source powder.

[0088] The technical effect of this is: the dispersant prevents the diffusion source powder in the organic slurry from re-aggregating, lowers the fineness of the organic slurry itself, and improves the consistency of weight gain during screen printing.

[0089] In a preferred embodiment of the present invention, the anti-settling agent in the neodymium iron boron screen printing organic slurry comprises one or two of polyamide wax, polyethylene wax, organic bentonite, fumed silica, or a mixture of various materials.

[0090] Preferably, the anti-settling agent comprises one or a mixture of both of polyamide wax and polyethylene wax, and the anti-settling agent can be completely decomposed at high temperatures and reduces C residue on the magnet surface during high-temperature grain boundary diffusion. The technical effect is that the anti-settling agent improves the static stability of the organic slurry, suppresses the appearance of a layer, and further lowers the volatilization rate at room temperature.

[0091] In a preferred embodiment of the present invention, the synergist in the neodymium iron boron screen printing organic slurry is one or two or several of modified polyhydroxycarboxylic acid esters, BYK-SYNERGIST 2105, and BYK-SYNERGIST 2100.

[0092] Preferably, the synergist is a modified polyhydroxycarboxylic acid ester, and the addition of the synergist significantly improves the high-temperature drying rate of the organic slurry under the premise that it does not affect the room-temperature volatilization rate, thereby ensuring the realization of a gradient volatilization rate.

[0093] The technical effect of this is: the above-mentioned synergist can improve the network structure of the organic carrier.

[0094] In a preferred embodiment of the present invention, the weight percentage of each component in the neodymium iron boron screen printing organic slurry is:

[0095] The pure metal powder is 65% to 75%;

[0096] One or two or more of propylene glycol phenyl ether, DBE, and propylene glycol methyl ether acetate are 10% to 30%;

[0097] One or two or more of ethylcellulose, polyvinyl butyral, and polyester resin are 0.4% to 4%;

[0098] One or two or more of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide are 0% to 3%;

[0099] One or two or more of the modified polyhydroxycarboxylic acid esters, BYK-SYNERGIST 2105, and BYK-SYNERGIST 2100 are 0% to 2%.

[0100] In a preferred embodiment of the present invention, the weight percentage of each component in the neodymium iron boron screen printing organic slurry is:

[0101] The alloy powder is 70% to 80%;

[0102] One or two or more of propylene glycol phenyl ether, DBE, and propylene glycol methyl ether acetate are 20% to 30%;

[0103] One or two or more of acrylic resin, polyurethane, and polyester resin are 0.4% to 5%;

[0104] One or two or more of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide are 0% to 3%;

[0105] One or both of polyamide wax and polyethylene wax are 0% to 2%;

[0106] One or two or more of the modified polyhydroxycarboxylic acid esters, BYK-SYNERGIST 2105, and BYK-SYNERGIST 2100 are 0% to 2%.

[0107] In a preferred embodiment of the present invention, the weight percentage of each component in the neodymium iron boron screen printing organic slurry is:

[0108] The heavy rare earth powder is 60% to 80%;

[0109] One or both of DBE and propylene glycol methyl ether acetate are 10% to 30%;

[0110] One or two or more of vinyl chloride resin, polyester resin, and polyurethane are 0.4% to 4%;

[0111] One or two or more of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide are 0% to 3%;

[0112] One or both of polyamide wax and polyethylene wax are 0% to 2%;

[0113] One or two or more of the modified polyhydroxycarboxylic acid esters, BYK-SYNERGIST 2105, and BYK-SYNERGIST 2100 are 0% to 2%.

[0114] Referring to FIG. 1, a second embodiment of the present invention provides a method for producing an organic slurry having a gradient volatilization rate as described above, and comprises the following:

[0115] Rare earth powder, organic solvent, resin, dispersant and / or antisettling agent and / or booster are each weighed according to weight percentage.

[0116] The weighed rare earth powder, organic solvent, resin, dispersant and / or antisediment and / or booster are sequentially placed into a stirrer and stirred at a speed of 600 r / min to 1200 r / min for 0.25 to 6 hours under constant temperature conditions of 20 to 70℃, and then cooled to room temperature to obtain an organic carrier.

[0117] The technical effect of this is: the obtained organic carrier is uniform and free of aggregated substances.

[0118] The above organic carrier and weighed rare earth powder are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 1000 r / min to 4000 r / min for 0.25 to 1 hour to obtain a coarse organic slurry.

[0119] The technical effect of this is: the obtained coarse organic slurry is bubble-free and uniformly dispersed.

[0120] The above coarse organic slurry is transferred to a three-roll grinder with adjustable spacing and ground 1 to 3 times to obtain a fine organic slurry.

[0121] The technical effect of this is: the fineness of the obtained fine organic slurry is less than 5 μm.

[0122] Specifically, the effects of the embodiment of the present invention are explained in more detail through the following examples and comparative examples. The ratios of various components in each example are as shown in Table 1.

[0123] number Diffusion source powder Organic solvent profit Dispersant Anti-settling agent Uplifter 1 70% Dy 80 Ni 20 Diffusion source powder 15% propylene glycol methyl ether acetate, 10% DBE 1% vinyl chloride resin, 2% polyester resin 2% sodium polyacrylate 0 0 2 70% Tb 83 Cu7Al 10 Diffusion source powder 10% methyl isobutanone, 12% polyester resin 2% acrylic resin 0.4% polyvinyl pyrrolidone, 0.6% polyvinyl amide 3% Organic Bentonite 2%BYK-SYNERGIST 2100 3 70% Dy Diffusion Source Powder 10% propylene glycol, 16% methyl ether acetate 3% polyester resin 0 0 1% modified polyhydroxycarboxylic acid ester 4 70%Pr 90 Al5Ga5 diffusion source powder 11% methyl isobutanone, 11% polyester resin 0.5% polyurethane, 1.5% polyester resin 0.5% polyvinyl pyrrolidone, 0.5% polyvinyl amide 1% polyamide wax, 1% polyethylene wax 3%BYK-SYNERGIST 2105 5 70% Dy 80 Ni 20 Diffusion source powder 12% propylene glycol methyl ether acetate, 12.5% ​​DBE 1% vinyl chloride resin, 2% polyester resin 2% sodium polyacrylate 0 0.5% modified polyhydroxycarboxylic acid ester 6 60% TbH diffusion source powder 35% propylene glycol phenyl ether 5% ethylcellulose 0 0 0 7 70%DyO 23% propylene glycol methyl ether acetate 1% polyester resin 1% Polyvinyl Pyrrolidone 0.5% organic bentonite, 1.5% fumed silica 2%BYK-SYNERGIST 2100 8 90% TbH diffusion source powder 8% propylene glycol phenyl ether 2% ethylcellulose 0 0 0 9 70% TbF Diffusion Source Powder 12% propylene glycol methyl ether acetate, 10.5% DBE 1.5% vinyl chloride resin, 1.5% polyester resin 2% sodium polyacrylate 0 2.5% Modified Polyhydroxycarboxylic Acid Ester 10 70%TbO 20% propylene glycol methyl ether acetate 4% polyester resin 1% Polyvinyl Pyrrolidone 0.5% organic bentonite, 1.5% fumed silica 2%BYK-SYNERGIST 2100 11 70% Tb diffusion source powder 24%DBE 4% Polyvinyl Butyral 1% polyethylene glycol 0 1% modified polyhydroxycarboxylic acid ester 12 50% TbH diffusion source powder 44% propylene glycol phenyl ether 6% ethylcellulose 0 0 0 13 70% Dy Diffusion Source Powder 12% propylene glycol, 12% methyl ether acetate 3% polyester resin 2% Polyvinyl Pyrrolidone 0 1% modified polyhydroxycarboxylic acid ester 14 70% Tb diffusion source powder 15% DBE + 12.6% Polyurethane 0.4% Polyvinyl Butyral 1% polyethylene glycol 0 1% modified polyhydroxycarboxylic acid ester 15 70% TbF Diffusion Source Powder 11% propylene glycol methyl ether acetate, 12% DBE 1.5% vinyl chloride resin, 1.5% polyester resin 2% sodium polyacrylate 0 2% Modified Polyhydroxycarboxylic Acid Ester 16 70% Tb 60 Ni 40 Diffusion source powder 10% propylene glycol methyl ether acetate, 13.5% DBE 2% vinyl chloride resin, 1% polyester resin 2% sodium polyacrylate 0 1.5% modified polyhydroxycarboxylic acid ester 17 70%TbO 23% propylene glycol methyl ether acetate 1% polyester resin 1% Polyvinyl Pyrrolidone 0.5% organic bentonite, 1.5% fumed silica 2%BYK-SYNERGIST 2100 18 70% Dy Diffusion Source Powder 9% propylene glycol, 12% methyl ether acetate 3% polyester resin 5% Polyvinyl Pyrrolidone 0 1% modified polyhydroxycarboxylic acid ester 19 15%Tb 82 Fe 18 、25%La 80 Al 20 30% Ce 80 Fe 20 Diffusion source powder 10% propylene glycol, 12% methyl ether acetate 2% polyester resin 1% Polyvinyl Pyrrolidone 0.5% organic bentonite, 1.5% fumed silica 1.5% Modified Polyhydroxycarboxylic Acid Ester, 1.5% BYK-SYNERGIST 2108 20 5%Nd 90 Cu5Al5, 60%Dy 90 Cu5Al5, 5%TbF diffusion source powder 10% propylene glycol, 12% methyl ether acetate 2% polyester resin 1% Polyvinyl Pyrrolidone 1% polyamide wax, 1% polyethylene wax 2% modified polyhydroxycarboxylic acid ester, 1% BYK-SYNERGIST 2107 21 5% Nd 90 Cu5Al5, 50%Dy 90 Cu5Al5, 15%Dy 80 Fe 20 Diffusion source powder 22% Methyl Isobutanone 2% acrylic resin 0.5% polyvinyl pyrrolidone, 0.5% polyvinyl amide 2% polyamide wax 3%BYK-SYNERGIST 2105 22 80% TbH diffusion source powder 17% propylene glycol phenyl ether 3% ethylcellulose 0 0 0 23 10%Tb、20%Nd 90 Cu5Al5, 40%Tb 90 Cu5Ho5 diffusion source powder 10% methyl isobutanone, 12% polyester resin 0.5% polyurethane, 1.5% polyester resin 0.6% polyvinyl pyrrolidone, 0.4% polyvinyl amide 0.5% polyamide wax, 1.5% polyethylene wax 3%BYK-SYNERGIST 2105 24 70% Tb 83 Cu7Al 10 Diffusion source powder 22% Methyl Isobutanone 3% acrylic resin 0.5% polyvinyl pyrrolidone, 0.5% polyvinyl amide 2% polyamide wax 2%BYK-SYNERGIST 2100 25 70% TbF Diffusion Source Powder 10% propylene glycol methyl ether acetate, 12% DBE 2% vinyl chloride resin, 1% polyester resin 2% sodium polyacrylate 0 3% Modified Polyhydroxycarboxylic Acid Ester 26 70% Tb diffusion source powder 22%DBE 6% Polyvinyl Butyral 1% polyethylene glycol 0 1% modified polyhydroxycarboxylic acid ester 27 70% Tb diffusion source powder 23%DBE 5% Polyvinyl Butyral 1% polyethylene glycol 0 1% modified polyhydroxycarboxylic acid ester 28 70% Tb diffusion source powder 10% DBE + 16% Polyurethane 2% Polyvinyl Butyral 1% polyethylene glycol 0 1% modified polyhydroxycarboxylic acid ester 29 70%Dy 80 Ni 20 Diffusion source powder 11% propylene glycol methyl ether acetate, 12% DBE 3% polyester resin 2% Polyvinyl Pyrrolidone 0 1% modified polyhydroxycarboxylic acid ester 30 70% Tb diffusion source powder 10% DBE + 17% Polyurethane 1% Polyvinyl Butyral 1% polyethylene glycol 0 1% modified polyhydroxycarboxylic acid ester 31 70%Tb 83 Cu7Al 10 Diffusion source powder 22% Methyl Isobutanone 3% acrylic resin 0.5% polyvinyl pyrrolidone, 0.5% polyvinyl amide 1% polyamide wax 3%BYK-SYNERGIST 2100 32 70%TbO 22% propylene glycol methyl ether acetate 2% polyester resin 2% Polyvinyl Pyrrolidone 0.5% organic bentonite, 1.5% fumed silica 2%BYK-SYNERGIST 2100 33 30%Nd 90 Cu5Al5, 20%Y 80 Fe 20 20% Tb diffusion source powder 10% propylene glycol methyl ether acetate, 12% DBE 0.5% vinyl chloride resin, 1.5% polyester resin 1% sodium polyacrylate 2% polyamide wax 1% modified polyhydroxycarboxylic acid ester, 2% BYK-SYNERGIST 2105 34 70%DyO 22% propylene glycol methyl ether acetate 2% polyester resin 1% Polyvinyl Pyrrolidone 0.5% organic bentonite, 1.5% fumed silica 2%BYK-SYNERGIST 2100 35 70%Dy 80 Ni 20 Diffusion source powder 11% propylene glycol methyl ether acetate, 13% DBE 2% vinyl chloride resin, 1% polyester resin 2% sodium polyacrylate 0 1% modified polyhydroxycarboxylic acid ester 36 70%DyO 20% propylene glycol methyl ether acetate 4% polyester resin 1% Polyvinyl Pyrrolidone 0.5% organic bentonite, 1.5% fumed silica 2%BYK-SYNERGIST 2100 37 70% Dy Diffusion Source Powder 11% propylene glycol, 12% methyl ether acetate 3% polyester resin 3% Polyvinyl Pyrrolidone 0 1% modified polyhydroxycarboxylic acid ester 38 10%Nd 90 Cu5Al5, 40%Dy 90 Cu5Al5, 20%Dy 80 Fe 20 Diffusion source powder 11% propylene glycol methyl ether acetate, 11% DBE 1% vinyl chloride resin, 1% polyester resin 1% sodium polyacrylate 2% polyamide wax 1% modified polyhydroxycarboxylic acid ester, 2% BYK-SYNERGIST 2106 39 70% Dy Diffusion Source Powder 10% propylene glycol, 12% methyl ether acetate 3% polyester resin 4% Polyvinyl Pyrrolidone 0 1% modified polyhydroxycarboxylic acid ester 40 70% TbH diffusion source powder 26% propylene glycol phenyl ether 4% ethylcellulose 0 0 0 41 70% Dy Diffusion Source Powder 15% propylene glycol, 10% methyl ether acetate 3% polyester resin 1% Polyvinyl Pyrrolidone 0 1% modified polyhydroxycarboxylic acid ester 42 70% Tb diffusion source powder 25%DBE 3% Polyvinyl Butyral 1% polyethylene glycol 0 1% modified polyhydroxycarboxylic acid ester

[0124] Example 1

[0125] 70%Dy 80 Ni20 Diffusion source powder, 15% propylene glycol methyl ether acetate, 10% DBE, 1% vinyl chloride resin, 2% polyester resin, and 2% sodium polyacrylate were weighed in weight percentage, and among them, Dy 80 Ni 20 The particle size of the diffusion source powder is D50=2.83μm;

[0126] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, and sodium polyacrylate are sequentially placed into a stirrer and stirred at a speed of 1200 r / min for 5 hours under constant temperature conditions of 60℃ to prepare a uniform and non-aggregated organic carrier;

[0127] Dy 80 Ni 20 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0128] Example 2

[0129] 70%Tb 80 Cu7Al 10 Diffusion source powder, 10% methyl isobutanone, 2% ethylcellulose, 12% polyester resin, 2% acrylic resin, 0.4% polyvinylpyrrolidone, 0.6% polyvinylamide, 3% organic bentonite, and 2% BYK-SYNERGIST 2100 were weighed in weight percentage, and among them, Tb 80 Cu 10 Al 10 The particle size of the diffusion source powder is D50=2.54μm;

[0130] Methyl isobutanone, ethylcellulose, polyester resin, acrylic resin, polyvinylpyrrolidone, polyvinylamide, organic bentonite, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 25 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0131] Tb 80 Cu 10 Al 10 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0132] Example 3

[0133] 70% Dy diffusion source powder, 10% propylene glycol, 16% methyl ether acetate, 3% polyester resin, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Dy diffusion source powder is D50=2.31μm;

[0134] Propylene glycol, methyl ether acetate, polyester resin, and modified polyhydroxycarboxylic acid ester are sequentially placed into a stirrer and stirred at a speed of 900 r / min for 6 hours under a constant temperature of 50℃ to prepare a uniform and non-aggregated organic carrier;

[0135] Dy diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2300 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0136] Example 4

[0137] 70%Pr 90Al5Ga5 diffusion source powder, 11% methyl isobutanone, 11% polyester resin, 0.5% polyurethane, 1.5% polyester resin, 0.5% polyvinylpyrrolidone, 0.5% polyvinylamide, 1% polyamide wax, 1% polyethylene wax, and 3% BYK-SYNERGIST 2105 were weighed in weight percentage, and among them, Pr 90 The particle size of the Al5Ga5 diffusion source powder is D50=1.89μm;

[0138] Methyl isobutanone, polyester resin, polyurethane, polyester resin, polyvinylpyrrolidone, polyvinylamide, polyamide wax, polyethylene wax, and BYK-SYNERGIST 2105 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 1 hour under constant temperature conditions of 30℃ to prepare a uniform and non-aggregated organic carrier;

[0139] Pr 90 Al5Ga5 diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0140] Example 5

[0141] 70%Dy 80 Ni 20 Diffusion source powder, 12% propylene glycol methyl ether acetate, 12.5% ​​DBE, 1% vinyl chloride resin, 2% polyester resin, 2% sodium polyacrylate, and 0.5% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, and among them, Dy 80 Ni 20 The particle size of the diffusion source powder is D50=2.5μm;

[0142] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, sodium polyacrylate, and modified polyhydroxycarboxylic acid ester were sequentially placed into a stirrer and stirred at a speed of 1000 r / min for 6 hours under constant temperature conditions of 60℃ to prepare a uniform and non-aggregated organic carrier;

[0143] Dy 80 Ni 20 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground three times to obtain an organic slurry with a fineness of less than 5 μm.

[0144] Example 6

[0145] 60% Tb-H diffusion source powder, 35% propylene glycol phenyl ether, and 5% ethylcellulose were weighed in weight percentage, wherein the particle size of the Tb-H diffusion source powder is D50=1.99μm;

[0146] Propylene glycol phenyl ether and ethyl cellulose are sequentially added to a stirrer and stirred at a speed of 900 r / min for 15 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0147] Tb-H diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2000 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0148] Example 7

[0149] 70% DyO diffusion source powder, 23% propylene glycol methyl ether acetate, 1% polyester resin, 1% polyvinyl pyrrolidone, 0.5% organic bentonite, 1.5% fumed silica, and 2% BYK-SYNERGIST 2100 were weighed in weight percentage, wherein the particle size of the DyO diffusion source powder is D50=2.27μm;

[0150] Propylene glycol methyl ether acetate, polyester resin, polyvinylpyrrolidone, organic bentonite, fumed silica, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 4 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0151] DyO diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 30 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground three times to obtain an organic slurry with a fineness of less than 5 μm.

[0152] Example 8

[0153] 90% TbH diffusion source powder, 8% propylene glycol phenyl ether, and 2% ethylcellulose are weighed in weight percentage, wherein the particle size of the TbH diffusion source powder is D50 < 2.5 μm;

[0154] Propylene glycol phenyl ether and ethyl cellulose are sequentially added to a stirrer and stirred at a speed of 900 r / min for 15 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0155] Tb-H diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2500 r / min for 50 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0156] Example 9

[0157] 70% TbF diffusion source powder, 12% propylene glycol methyl ether acetate, 10.5% DBE, 1.5% vinyl chloride resin, 1.5% polyester resin, 2% sodium polyacrylate, and 2.5% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb80Ni20 diffusion source powder is D50=2.33μm;

[0158] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, sodium polyacrylate, and modified polyhydroxycarboxylic acid ester are sequentially placed into a stirrer and stirred at a speed of 1000 r / min for 5 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0159] TbF diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground three times to obtain an organic slurry with a fineness of less than 5 μm.

[0160] Example 10

[0161] 70% TbO diffusion source powder, 20% propylene glycol methyl ether acetate, 4% polyester resin, 1% polyvinyl pyrrolidone, 0.5% organic bentonite, 1.5% fumed silica, and 2% BYK-SYNERGIST 2100 were weighed in weight percentage, wherein the particle size of the TbO diffusion source powder is D50 = 2.17 μm;

[0162] Propylene glycol methyl ether acetate, polyester resin, polyvinylpyrrolidone, organic bentonite, fumed silica, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 5.5 hours under constant temperature conditions of 60℃ to prepare a uniform and non-aggregated organic carrier;

[0163] TbO diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 40 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground three times to obtain an organic slurry with a fineness of less than 5 μm.

[0164] Example 11

[0165] 70% Tb diffusion source powder, 24% DBE, 4% polyvinyl butyral, 1% polyethylene glycol, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb diffusion source powder is D50 = 1.63 μm;

[0166] DBE, polyvinyl butyral, polyethylene glycol, and modified polyhydroxycarboxylic acid ester were sequentially added to a stirrer and stirred at a speed of 900 r / min for 15 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0167] Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2000 r / min for 15 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0168] Example 12

[0169] 50% Tb-H diffusion source powder, 44% propylene glycol phenyl ether, and 6% ethylcellulose were weighed in weight percentage, wherein the particle size of the Tb-H diffusion source powder is D50 = 2.43 μm;

[0170] Propylene glycol phenyl ether and ethyl cellulose are sequentially added to a stirrer and stirred at a speed of 900 r / min for 15 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0171] Tb-H diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2000 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0172] Example 13

[0173] 70% Dy diffusion source powder, 12% propylene glycol, 12% methyl ether acetate, 3% polyester resin, 2% polyvinyl pyrrolidone, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Dy diffusion source powder is D50 = 1.67 μm;

[0174] Propylene glycol, methyl ether acetate, polyester resin, polyvinylpyrrolidone, and modified polyhydroxycarboxylic acid ester are sequentially added to a stirrer and stirred at a speed of 1000 r / min for 6 hours under constant temperature conditions of 45℃ to prepare a uniform and non-aggregated organic carrier;

[0175] Dy diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2300 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0176] Example 14

[0177] 70% Tb diffusion source powder, 15% DBE, 12.6% polyurethane, 0.4% polyvinyl butyral, 1% polyethylene glycol, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb diffusion source powder is D50 = 1.84 μm;

[0178] DBE, polyurethane, polyvinyl butyral, polyethylene glycol, and modified polyhydroxycarboxylic acid ester are sequentially added to a stirrer and stirred at a speed of 900 r / min for 20 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0179] Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 30 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0180] Example 15

[0181] 70% TbF diffusion source powder, 11% propylene glycol methyl ether acetate, 12% DBE, 1.5% vinyl chloride resin, 1.5% polyester resin, 2% sodium polyacrylate, and 2% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb80Ni20 diffusion source powder is D50 = 2.45 μm;

[0182] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, sodium polyacrylate, and modified polyhydroxycarboxylic acid ester were sequentially placed into a stirrer and stirred at a speed of 1200 r / min for 5 hours under constant temperature conditions of 70℃ to prepare a uniform and non-aggregated organic carrier;

[0183] TbF diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 40 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0184] Example 16

[0185] 70% Tb60Ni40 diffusion source powder, 10% propylene glycol methyl ether acetate, 13.5% DBE, 2% vinyl chloride resin, 1% polyester resin, 2% sodium polyacrylate, and 1.5% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb60Ni40 diffusion source powder is D50 = 2.25 μm;

[0186] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, sodium polyacrylate, and modified polyhydroxycarboxylic acid ester were sequentially placed into a stirrer and stirred at a speed of 1200 r / min for 5 hours under constant temperature conditions of 65℃ to prepare a uniform and non-aggregated organic carrier;

[0187] Tb60Ni40 diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0188] Example 17

[0189] 70% TbO diffusion source powder, 23% propylene glycol methyl ether acetate, 1% polyester resin, 1% polyvinyl pyrrolidone, 0.5% organic bentonite, 1.5% fumed silica, and 2% BYK-SYNERGIST 2100 were weighed in weight percentage, wherein the particle size D50 of the TbO diffusion source powder is D50 < 3 μm;

[0190] Propylene glycol methyl ether acetate, polyester resin, polyvinylpyrrolidone, organic bentonite, fumed silica, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 4 hours under constant temperature conditions of 45℃ to prepare a uniform and non-aggregated organic carrier;

[0191] TbO diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 35 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0192] Example 18

[0193] 70% Dy diffusion source powder, 9% propylene glycol, 12% methyl ether acetate, 3% polyester resin, 5% polyvinyl pyrrolidone, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Dy diffusion source powder is D50 = 2.46 μm;

[0194] Propylene glycol, methyl ether acetate, polyester resin, polyvinylpyrrolidone, and modified polyhydroxycarboxylic acid ester are sequentially placed into a stirrer and stirred at a speed of 1200 r / min for 5 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0195] Dy diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2300 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0196] Example 19

[0197] 5%Tb 82 Fe 18 , 25%La 80 Al 20 , 30%Ce 80 Fe 20Diffusion source powder, 10% propylene glycol, 12% methyl ether acetate, 2% polyester resin, 1% polyvinyl pyrrolidone, 0.5% organic bentonite, 1.5% fumed silica, 1.5% modified polyhydroxycarboxylic acid ester, and 1.5% BYK-SYNERGIST 2100 were weighed in weight percentage, and among them, Tb 82 Fe 18 , La 80 Al 20 , Ce 80 Fe 20 The particle size D50 of the diffusion source powder is 2.33, 2.17, and 2.48 μm, respectively;

[0198] Propylene glycol, methyl ether acetate, polyester resin, polyvinylpyrrolidone, organic bentonite, fumed silica, modified polyhydroxycarboxylic acid ester, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 5 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0199] Tb 82 Fe 18 , La 80 Al 20 , Ce 80 Fe 20 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 30 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0200] Example 20

[0201] 5%Nd 90 Cu5Al5, 60%Dy 90Cu5Al5, 5% TbF diffusion source powder, 10% propylene glycol, 12% methyl ether acetate, 2% polyester resin, 1% polyvinyl pyrrolidone, 1% polyamide wax, 1% polyethylene wax, 2% modified polyhydroxycarboxylic acid ester, and 1% BYK-SYNERGIST 2100 were weighed in weight percentage, and among them, Nd 90 Cu5Al5, Dy 90 The particle size D50 of the Cu5Al5 and TbF diffusion source powders is 1.73, 2.07, and 1.88 μm, respectively;

[0202] Propylene glycol, methyl ether acetate, polyester resin, polyvinylpyrrolidone, polyamide wax, polyethylene wax, modified polyhydroxycarboxylic acid ester, and BYK-SYNERGIST 2100 were sequentially added to a stirrer and stirred at a speed of 1000 r / min for 5 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0203] Nd 90 Cu5Al5, Dy 90 Cu5Al5, TbF diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 30 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0204] Example 21

[0205] 5%Nd 90 Cu5Al5, 50%Dy 90 Cu5Al5, 15%Dy 80 Fe 20 Diffusion source powder, 22% methyl isobutanone, 2% acrylic resin, 0.5% polyvinylpyrrolidone, 0.5% polyvinylamide, 2% polyamide wax, and 3% BYK-SYNERGIST 2105 were weighed in weight percentage, and among them, Nd 90 Cu5Al5, Dy 90 Cu5Al5, Dy80 Fe 20 The particle size D50 of the diffusion source powder is 2.02, 2.13, and 2.27 μm, respectively;

[0206] Methyl isobutanone, acrylic resin, polyvinylpyrrolidone, polyvinylamide, polyamide wax, and BYK-SYNERGIST 2105 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 20 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0207] Nd 90 Cu5Al5, Dy 90 Cu5Al5, Dy 80 Fe 20 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 40 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0208] Example 22

[0209] 80% Tb-H diffusion source powder, 17% propylene glycol phenyl ether, and 3% ethylcellulose were weighed in weight percentage, wherein the particle size of the Tb-H diffusion source powder is D50 = 1.67 μm;

[0210] Propylene glycol phenyl ether and ethyl cellulose are sequentially added to a stirrer and stirred at a speed of 900 r / min for 15 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0211] Tb-H diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2000 r / min for 45 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground three times to obtain an organic slurry with a fineness of less than 5 μm.

[0212] Example 23

[0213] 10%Tb, 20%Nd 90 Cu5Al5, 40%Tb 90 Cu5Ho5 diffusion source powder, 10% methyl isobutanone, 12% polyester resin, 0.5% polyurethane, 1.5% polyester resin, 0.6% polyvinylpyrrolidone, 0.4% polyvinylamide, 0.5% polyamide wax, 1.5% polyethylene wax, and 3% BYK-SYNERGIST 2105 were weighed in weight percentage, and among them, Tb, Nd 90 Cu5Al5, Tb 90 The particle size D50 of the Cu5Ho5 diffusion source powder is 1.45, 1.56, and 1.73 μm, respectively;

[0214] Methyl isobutanone, polyester resin, polyurethane, polyester resin, polyvinylpyrrolidone, polyvinylamide, polyamide wax, polyethylene wax, and BYK-SYNERGIST 2105 were sequentially placed in a stirrer and stirred at a speed of 1200 r / min for 6 hours under constant temperature conditions of 70℃ to prepare a uniform and non-aggregated organic carrier;

[0215] Tb, Nd 90 Cu5Al5, Tb 90 Cu5Ho5 diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a 3-roll grinder and ground 3 times to obtain an organic slurry with a fineness of less than 5 μm.

[0216] Example 24

[0217] 70%Tb 80 Cu 10 Al 10 Diffusion source powder, 22% methyl isobutanone, 3% acrylic resin, 0.5% polyvinylpyrrolidone, 0.5% polyvinylamide, 2% polyamide wax, and 2% BYK-SYNERGIST 2100 were weighed in weight percentage, and among them, Tb 80 Cu 10 Al10 The particle size of the diffusion source powder is D50 <= 2.17 μm;

[0218] Methyl isobutanone, acrylic resin, polyvinylpyrrolidone, polyvinylamide, polyamide wax, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 25 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0219] Tb 80 Cu 10 Al 10 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0220] Example 25

[0221] 70% TbF diffusion source powder, 10% propylene glycol methyl ether acetate, 12% DBE, 2% vinyl chloride resin, 1% polyester resin, 2% sodium polyacrylate, and 3% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb80Ni20 diffusion source powder is D50 = 2.36 μm;

[0222] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, sodium polyacrylate, and modified polyhydroxycarboxylic acid ester were sequentially placed into a stirrer and stirred at a speed of 1200 r / min for 4 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0223] TbF diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0224] Example 26

[0225] 70% Tb diffusion source powder, 22% DBE, 6% polyvinyl butyral, 1% polyethylene glycol, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb diffusion source powder is D50 = 2.53 μm;

[0226] DBE, polyvinyl butyral, polyethylene glycol, and modified polyhydroxycarboxylic acid ester were sequentially added to a stirrer and stirred at a speed of 1000 r / min for 30 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0227] Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2000 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0228] Example 27

[0229] 70% Tb diffusion source powder, 23% DBE, 5% polyvinyl butyral, 1% polyethylene glycol, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb diffusion source powder is D50 = 1.93 μm;

[0230] DBE, polyvinyl butyral, polyethylene glycol, and modified polyhydroxycarboxylic acid ester were sequentially added to a stirrer and stirred at a speed of 900 r / min for 25 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0231] Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2000 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0232] Example 28

[0233] 70% Tb diffusion source powder, 10% DBE, 16% polyurethane, 2% polyvinyl butyral, 1% polyethylene glycol, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb diffusion source powder is D50 = 2.07 μm;

[0234] DBE, polyurethane, polyvinyl butyral, polyethylene glycol, and modified polyhydroxycarboxylic acid ester were sequentially added to a stirrer and stirred at a speed of 600 r / min for 40 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0235] Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 35 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0236] Example 29

[0237] 70%Dy 80 Ni 20 Diffusion source powder, 11% propylene glycol methyl ether acetate, 12% DBE, 3% polyester resin, 2% polyvinyl pyrrolidone, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, and among them, Dy 80 Ni 20 The particle size of the diffusion source powder is D50 = 2.5 μm;

[0238] Propylene glycol methyl ether acetate, DBE, polyester resin, polyvinylpyrrolidone, and modified polyhydroxycarboxylic acid ester were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 4 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0239] Dy 80 Ni 20 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0240] Example 30

[0241] 70% Tb diffusion source powder, 10% DBE, 17% polyurethane, 1% polyvinyl butyral, 1% polyethylene glycol, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb diffusion source powder is D50 = 2.36 μm;

[0242] DBE, polyurethane, polyvinyl butyral, polyethylene glycol, and modified polyhydroxycarboxylic acid ester were sequentially added to a stirrer and stirred at a speed of 900 r / min for 20 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0243] Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 30 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0244] Example 31

[0245] 70%Tb 80 Cu 10 Al 10Diffusion source powder, 22% methyl isobutanone, 3% acrylic resin, 0.5% polyvinylpyrrolidone, 0.5% polyvinylamide, 1% polyamide wax, and 3% BYK-SYNERGIST 2100 were weighed in weight percentage, and among them, Tb 80 Cu 10 Al 10 The particle size of the diffusion source powder is D50 = 1.91 μm;

[0246] Methyl isobutanone, acrylic resin, polyvinylpyrrolidone, polyvinylamide, polyamide wax, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 25 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0247] Tb 80 Cu 10 Al 10 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 45 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground three times to obtain an organic slurry with a fineness of less than 5 μm.

[0248] Example 32

[0249] 70% TbO diffusion source powder, 22% propylene glycol methyl ether acetate, 2% polyester resin, 2% polyvinyl pyrrolidone, 0.5% organic bentonite, 1.5% fumed silica, and 2% BYK-SYNERGIST 2100 were weighed in weight percentage, wherein the particle size of the TbO diffusion source powder is D50 = 2.38 μm;

[0250] Propylene glycol methyl ether acetate, polyester resin, polyvinylpyrrolidone, organic bentonite, fumed silica, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 4 hours under constant temperature conditions of 45℃ to prepare a uniform and non-aggregated organic carrier;

[0251] TbO diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 30 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground three times to obtain an organic slurry with a fineness of less than 5 μm.

[0252] Example 33

[0253] 30%Nd 90 Cu5Al5, 20%Y 80 Fe 20 , 20% Tb diffusion source powder, 10% propylene glycol methyl ether acetate, 12% DBE, 0.5% vinyl chloride resin, 1.5% polyester resin, 1% acrylic resin, 2% polyamide wax, 1% modified polyhydroxycarboxylic acid ester, and 2% BYK-SYNERGIST 2105 were weighed in weight percentage, and among them, Nd 90 Cu5Al5, Y 80 Fe 20 The particle size D50 of the Tb diffusion source powder is 1.67, 1.85, and 2.02 μm, respectively;

[0254] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, acrylic resin, polyamide wax, modified polyhydroxycarboxylic acid ester, and BYK-SYNERGIST 2105 were sequentially added to a stirrer and stirred at a speed of 1200 r / min for 3 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0255] Nd 90 Cu5Al5, Y 80 Fe 20 , Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0256] Example 34

[0257] 70% DyO diffusion source powder, 22% propylene glycol methyl ether acetate, 2% polyester resin, 1% polyvinyl pyrrolidone, 0.5% organic bentonite, 1.5% fumed silica, and 2% BYK-SYNERGIST 2100 were weighed in weight percentage, wherein the particle size of the TbO diffusion source powder is D50 = 2.32 μm;

[0258] Propylene glycol methyl ether acetate, polyester resin, polyvinylpyrrolidone, organic bentonite, fumed silica, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 5 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0259] DyO diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 30 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0260] Example 35

[0261] 70%Dy 80 Ni 20 Diffusion source powder, 11% propylene glycol methyl ether acetate, 13% DBE, 2% vinyl chloride resin, 1% polyester resin, 2% sodium polyacrylate, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb80Ni20 diffusion source powder is D50 = 1.99 μm;

[0262] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, sodium polyacrylate, and modified polyhydroxycarboxylic acid ester were sequentially placed into a stirrer and stirred at a speed of 1200 r / min for 6 hours under constant temperature conditions of 65℃ to prepare a uniform and non-aggregated organic carrier;

[0263] Dy 80 Ni 20 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 45 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0264] Example 36

[0265] 70% DyO diffusion source powder, 20% propylene glycol methyl ether acetate, 4% polyester resin, 1% polyvinyl pyrrolidone, 0.5% organic bentonite, 1.5% fumed silica, and 2% BYK-SYNERGIST 2100 were weighed in weight percentage, wherein the particle size of the TbO diffusion source powder is D50 = 2.35 μm;

[0266] Propylene glycol methyl ether acetate, polyester resin, polyvinylpyrrolidone, organic bentonite, fumed silica, and BYK-SYNERGIST 2100 were sequentially placed in a stirrer and stirred at a speed of 1200 r / min for 6 hours under constant temperature conditions of 79℃ to prepare a uniform and non-aggregated organic carrier;

[0267] TbO diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 30 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0268] Example 37

[0269] 70% Dy diffusion source powder, 11% propylene glycol, 12% methyl ether acetate, 3% polyester resin, 3% polyvinyl pyrrolidone, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Dy diffusion source powder is D50 = 1.96 μm;

[0270] Propylene glycol, methyl ether acetate, polyester resin, polyvinylpyrrolidone, and modified polyhydroxycarboxylic acid ester were sequentially placed in a stirrer and stirred at a speed of 900 r / min for 5 hours under constant temperature conditions of 70℃ to prepare a uniform and non-aggregated organic carrier;

[0271] Dy diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2300 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0272] Example 38

[0273] 10%Nd 90 Cu5Al5, 40%Dy 90 Cu5Al5, 20%Dy 80 Fe 20 Diffusion source powder, 11% propylene glycol methyl ether acetate, 11% DBE, 1% vinyl chloride resin, 1% polyester resin, 1% sodium polyacrylate, 2% polyamide wax, 1% modified polyhydroxycarboxylic acid ester, and 2% BYK-SYNERGIST 2105 were weighed in weight percentage, and among them, Nd 90 Cu5Al5, Dy 90 Cu5Al5, Dy 80 Fe 20 The particle size D50 of the diffusion source powder is 2.34, 2.47, and 2.35 μm, respectively;

[0274] Propylene glycol methyl ether acetate, DBE, vinyl chloride resin, polyester resin, sodium polyacrylate, polyamide wax, modified polyhydroxycarboxylic acid ester, and 2% BYK-SYNERGIST 2105 were sequentially added to a stirrer and stirred at a speed of 1000 r / min for 5 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0275] Nd 90 Cu5Al5, Dy 90 Cu5Al5, Dy 80 Fe 20 A diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2200 r / min for 35 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0276] Example 39

[0277] 70% Dy diffusion source powder, 10% propylene glycol, 12% methyl ether acetate, 3% polyester resin, 4% polyvinyl pyrrolidone, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Dy diffusion source powder is D50 = 1.97 μm;

[0278] Propylene glycol, methyl ether acetate, polyester resin, polyvinylpyrrolidone, and modified polyhydroxycarboxylic acid ester are sequentially placed in a stirrer and stirred at a speed of 1000 r / min for 4.5 hours under constant temperature conditions of 55℃ to prepare a uniform and non-aggregated organic carrier;

[0279] Dy diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2300 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a 3-roll grinder and ground 3 times to obtain an organic slurry with a fineness of less than 5 μm.

[0280] Example 40

[0281] 70% Tb-H diffusion source powder, 26% propylene glycol phenyl ether, and 4% ethylcellulose were weighed in weight percentage, wherein the particle size of the Tb-H diffusion source powder is D50 = 1.64 μm;

[0282] Propylene glycol phenyl ether and ethyl cellulose are sequentially added to a stirrer and stirred at a speed of 600 r / min for 15 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0283] Tb-H diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2000 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0284] Example 41

[0285] 70% Dy diffusion source powder, 15% propylene glycol, 10% methyl ether acetate, 3% polyester resin, 1% polyvinyl pyrrolidone, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Dy diffusion source powder is D50=2.06μm;

[0286] Propylene glycol, methyl ether acetate, polyester resin, polyvinylpyrrolidone, and modified polyhydroxycarboxylic acid ester were sequentially placed in a stirrer and stirred at a speed of 1200 r / min for 6 hours under constant temperature conditions of 45℃ to prepare a uniform and non-aggregated organic carrier;

[0287] Dy diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2300 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground twice to obtain an organic slurry with a fineness of less than 5 μm.

[0288] Example 42

[0289] 70% Tb diffusion source powder, 25% DBE, 3% polyvinyl butyral, 1% polyethylene glycol, and 1% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb diffusion source powder is D50 = 2.08 μm;

[0290] DBE, polyvinyl butyral, polyethylene glycol, and modified polyhydroxycarboxylic acid ester were sequentially added to a stirrer and stirred at a speed of 900 r / min for 20 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0291] Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed dispersed at a speed of 2000 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0292] Comparative Example 1

[0293] 60% Tb diffusion source powder, 35.7% anhydrous ethanol, 2% polyvinyl butyral, 1% polyvinyl pyrrolidone, 1% polyamide wax, and 0.3% modified polyhydroxycarboxylic acid ester were weighed in weight percentage, wherein the particle size of the Tb diffusion source powder is D50 < 3 μm;

[0294] Anhydrous ethanol, polyvinyl butyral, polyvinyl pyrrolidone, polyamide wax, and modified polyhydroxycarboxylic acid ester are sequentially added to a stirrer and stirred at a speed of 900 r / min for 15 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0295] Tb diffusion source powder and the prepared organic carrier are placed in a vacuum high-speed disperser and high-speed stirred at a speed of 2000 r / min for 25 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0296] Comparative Example 2

[0297] 80% TbNi diffusion source powder, 17.5% acetone, 1.5% polyvinyl butyral, and 1% polyethylene glycol are weighed in weight percentage, wherein the particle size of the TbNi diffusion source powder is D50 < 3 μm;

[0298] Acetone, polyvinyl butyral, and polyethylene glycol are sequentially added to a stirrer and stirred at a speed of 1000 r / min for 20 minutes under constant temperature conditions of 25℃ to prepare a uniform and non-aggregated organic carrier;

[0299] Weighed TbNi diffusion source powder and a prepared organic carrier are placed in a vacuum high-speed disperser and high-speed stirred at a speed of 2200 r / min for 15 minutes to pre-prepare an organic slurry; then, the organic slurry prepared by high-speed dispersion is transferred to a three-roll grinder and ground once to obtain an organic slurry with a fineness of less than 5 μm.

[0300] For the organic slurry for neodymium iron boron magnet screen printing having a gradient volatilization rate prepared in Examples 1-4 and the organic slurry prepared in Comparative Example 1-2, volatilization curves were tested by sequentially holding at 40, 80, and 120°C for 2 hours, and the results are as shown in FIGS. 2 and 3. Referring to FIG. 2, the volatilization rate of Examples 1-4 is very low at 40°C, with all values ​​being less than 0.15%, ensuring storage and printing stability; when the temperature increases to 120°C, the volatilization rate increases significantly, ensuring drying efficiency. Referring to FIG. 3, although Comparative Example 1-2 has a very high volatilization rate at high temperatures, the volatilization rates at 40°C exceed 10% and 40%, respectively, which seriously affects the stability of the organic slurry during printing and is disadvantageous for continuous production.

[0301] The organic slurry prepared in Example 1 was coated onto the surface of a neodymium iron boron magnet using a screen printing method and dried at 120°C for 10 minutes. After drying, the magnet coating was observed using a gold microscope as shown in Fig. 4. After drying, the coating uniformity was excellent, there were no distinct cracks or bubbles, and the bonding with gas was good, indicating that the volatilization rate of the organic material during the drying process was appropriate.

[0302] The organic slurry prepared in Examples 1-8 was coated onto the surface of a neodymium iron-boron magnet by screen printing, and after drying, the neodymium iron-boron magnet was heat-treated at 900°C for 5 hours and tempered at 500°C for 3 hours. The magnetic performance measured is as shown in FIG. 2. After diffusion, the residual magnetic reduction was all less than 0.3 kGs. It can be seen that the organic slurry does not affect the subsequent diffusion process.

[0303] number Residual magnetic reduction / kGs Example 1 0.23 Example 2 0.26 Example 3 0.12 Example 4 0.24 Example 5 0.20 Example 6 0.18 Example 7 0.27 Example 8 0.09

[0304] An embodiment of the present invention is intended to protect an organic slurry having a gradient volatilization rate and a method for manufacturing it, and has the following effects:

[0305] By forming a gradient of organic components and with the help of strong interaction of abrasives, the organic carrier forms a network structure, ensuring that the volatilization rate at room temperature is less than 0.05% / h and the volatilization rate at high temperature of 120°C is 1.2% / h or more, thereby realizing gradient volatilization of the slurry. The manufactured organic slurry for screen printing of rare earth permanent magnet materials has a low volatilization rate at room temperature, which can effectively prevent problems such as screen clogging and printing non-uniformity caused by the volatilization of organic solvents during printing; at high temperatures, the organic slurry has a high volatilization rate and a short curing time, which significantly reduces drying time, improves processing efficiency, and reduces the content of impurities such as oxygen and carbon introduced into the magnet during the curing and subsequent heat treatment steps.

[0306] It should be understood that the specific embodiments of the present invention described above are merely illustrative descriptions or interpretations of the principles of the present invention and do not constitute a limitation to the present invention. Accordingly, all modifications, equivalent substitutions, improvements, etc., made under conditions that do not depart from the spirit and scope of the present invention shall be included within the scope of protection of the present invention. Furthermore, the object of the claims of the present invention is to include all variations and modifications within the scope and boundaries of the claims or within an equivalent form thereof.

Claims

Claim 1 An organic slurry having a gradient volatilization rate, comprising rare earth powder, an organic solvent, and a resin, and further comprising a dispersant, an antisediment agent, and a promoter, wherein the weight percentage of each component is: the rare earth powder is 50% to 90%; the organic solvent is 8% to 44%; the resin is 0.4% to 6%; the dispersant is greater than 0 and less than or equal to 5%; the antisediment agent is greater than 0 and less than or equal to 3%; the antisediment agent comprises one or two or various mixtures of polyamide wax, polyethylene wax, organic bentonite, and fumed silica; the promoter is greater than 0 and less than or equal to 3%; and the promoter is a modified polyhydroxycarboxylic acid ester. Claim 2 An organic slurry having a gradient volatilization rate according to claim 1, characterized in that the rare earth powder comprises one or two mixtures of the following: a pure metal powder of a heavy rare earth element, an alloy powder containing a heavy rare earth or light rare earth element, and a heavy rare earth powder containing a hydride, fluoride, and oxide of a heavy rare earth element. Claim 3 An organic slurry having a gradient volatilization rate according to claim 2, wherein the pure metal powder comprises one or two or various mixtures of Tb, Dy, Ho, and Gd; and the alloy powder constitutes RexMy in mass percentage, wherein RE is one or two or various mixtures of Tb, Dy, Ho, Gd, Pr, Nd, La, Ce, and Y, and M is one or two or various mixtures of Ga, Cu, Al, Ni, and Fe, and 60≤x≤95, 5≤y≤40. Claim 4 An organic slurry having a gradient volatilization rate according to claim 1, characterized in that the particle size of the rare earth powder is D50 < 3μm. Claim 5 An organic slurry having a gradient volatilization rate according to claim 2, characterized in that the organic solvent comprises one or two or various mixtures of propylene glycol phenyl ether, DBE (dibasic acid ester), methyl isobutanone, and propylene glycol methyl ether acetate. Claim 6 An organic slurry having a gradient volatilization rate according to claim 5, characterized in that the resin comprises one or two or various mixtures of ethyl cellulose, polyvinyl butyral, acrylic resin, vinyl chloride resin, polyester resin, and polyurethane. Claim 7 An organic slurry having a gradient volatilization rate according to claim 6, characterized in that the dispersant comprises one or two or a mixture of polyvinyl butyral, polyvinyl pyrrolidone, sodium polyacrylate, and polyvinylamide. Claim 8 An organic slurry having a gradient volatilization rate, characterized in that, in claim 7, the weight percentage of each component is: pure metal powder is 65% to 75%; one or two or various of propylene glycol phenyl ether, DBE (dibasic acid ester), and propylene glycol methyl ether acetate is 10% to 30%; one or two or various of ethyl cellulose, polyvinyl butyral, and polyester resin is 0.4% to 4%; one or two or various of polyethylene glycol, polyvinyl pyrrolidone, and polyvinyl amide is greater than 0 and less than or equal to 3%; and modified polyhydroxycarboxylic acid ester is greater than 0 and less than or equal to 2%. Claim 9 An organic slurry having a gradient volatilization rate, characterized in that, in claim 7, the weight percentage of each component is: alloy powder is 70% to 80%; one or two or various of propylene glycol phenyl ether, DBE (dibasic acid ester), and propylene glycol methyl ether acetate is 20% to 30%; one or two or various of acrylic resin, polyurethane, and polyester resin is 0.4% to 5%; one or two or various of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide is greater than 0 and less than or equal to 3%; one or two of polyamide wax and polyethylene wax are greater than 0 and less than or equal to 2%; and modified polyhydroxycarboxylic acid ester is greater than 0 and less than or equal to 2%. Claim 10 An organic slurry having a gradient volatilization rate, characterized in that, in claim 7, the weight percentage of each component is: 60% to 80% for heavy rare earth powder; 10% to 30% for one or both of DBE (dibasic acid ester) and propylene glycol methyl ether acetate; 0.4% to 4% for one or both or various of vinyl chloride resin, polyester resin, and polyurethane; greater than 0 and 3% or less for one or two or various of polyethylene glycol, polyvinylpyrrolidone, and polyvinylamide; 0% to 2% for one or both of polyamide wax and polyethylene wax; and greater than 0 and 2% or less for modified polyhydroxycarboxylic acid ester. Claim 11 A method for preparing an organic slurry having a gradient volatilization rate as in any one of claims 1 to 10, comprising: weighing a rare earth powder, an organic solvent, a resin, a dispersant and / or an antisediment and / or a booster according to weight percentage; sequentially placing the weighed rare earth powder, organic solvent, resin, dispersant and / or antisediment and / or booster into a stirrer and stirring at a speed of 600 r / min to 1200 r / min for 0.25 to 6 hours under constant temperature conditions of 20 to 70°C, and then cooling to room temperature to obtain an organic carrier; placing the organic carrier and the weighed rare earth powder into a vacuum high-speed disperser and high-speed dispersing at a speed of 1000 r / min to 4000 r / min for 0.25 to 1 hour to obtain a coarse organic slurry; transferring the coarse organic slurry to a three-roll grinder with adjustable spacing and grinding 1 to 3 times to obtain a fine organic slurry. Method for manufacturing an organic slurry having a gradient volatilization rate. Claim 12 delete Claim 13 delete

Citation Information

Patent Citations

  • Preparation process of slurry for screen printing of sintered NdFeB (neodymium iron boron)

    CN113736312A

  • A composition of water-soluble paint marker and the manufacturing method thereof

    KR100994105B1

  • Coating slurry and preparation method of high-performance neodymium-iron-boron magnet

    CN114914077A

  • Method of manufacturing bond magnet, bond magnet, and manufacturing apparatus

    JP2009158860A